Efektifitas Penggunaan Flash Video Dalam Meningkatkan Ketrampilan Istima’ Mufrodat Siswa Kelas VII di Madrasah Tsanawiyyah Nahdlotul ‘Ulama Berbek Waru Sidoarjo : Efektifitas Penggunaan Flash Video Dalam Meningkatkan Ketrampilan Istima’ Mufrodat Siswa Sidoarjo - Faruq Abdul Muid; Abdussalam (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2021)
The development of technology that exists today cannot be denied its influence in the field of education. The computerization of learning media is already familiar. One of the popular learning media is flash video. The use of flash videos is expected to be able to attract more students' attention in the learning process and also make it easier for students to understand the lesson. Listening skills as the basis of language acquisition is one of the important points that must be considered by Arabic language teachers, most of whom pay little attention to this. This study was aimed to determine the effectiveness of flash video media in improving students' vocabulary listening skills. This research was conducted at MTs NU Berbek Waru Sidoarjo using quantitative research methods. The formulation of the problem from this research is as follows: 1. How is the istima' mufrodat skill of class VII students at the madrasah Tsanawiyyah nahdlotul 'ulama with waru sidoarjo?. How is the effectiveness of using